Morphemic Analysis as Imagined by Developmental Reading Textbooks: A Content Analysis of a Textbook Corpus. Issue 1 (2nd January 2017) - Roth, Daniel
Abstract : Although vocabulary instruction is a pressing need for postsecondary reading instructors, a minimal amount of current postsecondary scholarship addresses this need, and almost no current scholarship addresses the textbook tradition of morphemic analysis (MA). The present article reviews the literature on MA instruction and argues for teaching MA as a flexible strategy where students have metacognitive awareness of its workings/limitations. To investigate how textbooks teach MA, the present study applied qualitative content analysis to a corpus of widely adopted textbooks. Results show that textbooks generally favored the more flexible/metacognitive approach. It is concluded that textbooks are fairly well-informed by current scholarship on MA, but they need to explicitly state that MA does not work reliably and provide more exercises in which students practice applying MA to longer, more authentic texts.